O jovem e a violência: perspectivas de educação dual - Rosimar Serena Siqueira Esquinsan; Valdocir Antonio Esquinsani (EccoS – Revista Científica)
The text assumes that the media is – increasingly in today’s society – in charge of the construction and circulation of a set of images, codes and information, exercising leadership as opinion maker. Thus, this paper presents the results of a sur - vey on the impact of media in the construction of the educational agenda, specifically regarding the actions to deal with youth violence in the school environment. Part of a qualitative and quantitative research, anchored in the content analysis of 154 products of mass media, served in three major Brazilian magazines of national circulation: Veja , Isto É and Época , in the time frame from 2001 to 2011 , and from the examination of media products readings were established on the representations of violence / school and the different shares pledged to combat such violence involving specifically distinct perspec - tives of education for different groups of young people, tangent thus dualism education. In conclusion, the opinions formed by the media deserve detailed consideration by critics leading, in the case in question, the reflections on violence in the school environment in the context of dual education.